PENGEMBANGAN WEB INFORMASI DESA SIDO MAKMUR UNTUK MENINGKATKAN PELAYANAN MASYARAKAT - Bagus Satrio Utomo; Heriyanti Heriyanti; Malda Karindra; Pamuji Muhamad Jakak; Thoha Firdaus (CV. Denasya Smart Publisher, 2025)
This study aims to develop the Sido Makmur Village information website to improve the quality of public services, expand access to information, and encourage community participation in village development. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation. Data analysis used an interactive model consisting of data reduction, data presentation, and inductive conclusion drawing. The results showed that the development of the village website had a positive impact on administrative service efficiency, faster information delivery, and increased citizen engagement, particularly among the younger generation. The website also served as a strategic platform for documenting activities, presenting financial reports, and promoting village potential more widely. Despite challenges such as limited digital infrastructure and technical capacity of human resources, the desa-sidomakmur.com website proved to be an innovative solution in strengthening transparent and participatory village governance based on information technology.